Ownership Status of Land Rights from Reclamation Results by Foreign Legal Subject - Yosua Simon Suganda (Indonesian Journal of Law and Islamic Law (IJLIL), 2024)
Rapid population growth that did not accompany by an increase of land area can lead to a big problem in a long term, such as high land prices. Hence reclamation need to be done so it can help people to have a land with affordable price. However, reclamation can’t be done without following terms and conditions by the government. This writing made so we can know who is eligible to do the reclamation, what type of law subject can do reclamation. The writings use normative-juridicial research approach and qualitative-juridicial analysis method. By following all legal requirements person and entities law subject can do the reclamation, both local and foreign legal subject.